Wdr18 is required for Kupffer's vesicle formation and regulation of body asymmetry in zebrafish. - Wei Gao; Linjie Xu; Rui Guan; Xinxing Liu; Yuxiang Han; Qian Wu; Yi Xiao; Fei Qi; Zuoyan Zhu; Shuo Lin; Bo Zhang (PLoS ONE)
Correct specification of the left-right (L-R) axis is important for organ morphogenesis. Conserved mechanisms involving cilia rotation inside node-like structures and asymmetric Nodal signaling in the lateral plate mesoderm (LPM), which are important symmetry-breaking events, have been intensively studied. In zebrafish, the clustering and migration of dorsal forerunner cells (DFCs) is critical for the formation of the Kuppfer's vesicle (KV). However, molecular events underlying DFC clustering and migration are less understood. The WD-repeat proteins function in a variety of biological processes, including cytoskeleton assembly, intracellular trafficking, mRNA splicing, transcriptional regulation and cell migration. However, little is known about the function of WD-repeat proteins in L-R asymmetry determination. Here, we report the identification and functional analyses of zebrafish wdr18, a novel gene that encodes a WD-repeat protein that is highly conserved among vertebrate species. wdr18 was identified from a Tol2 transposon-mediated enhancer trap screen. Follow-up analysis of wdr18 mRNA expression showed that it was detected in DFCs or the KV progenitor cells and later in the KV at early somitogenesis stages. Morpholino knockdown of wdr18 resulted in laterality defects in the visceral organs, which were preceded by the mis-expression of Nodal-related genes, including spaw and pitx2. Examination of morphants at earlier stages revealed that the KV had fewer and shorter cilia which are immotile and a smaller cavity. We further investigated the organization of DFCs in wdr18 morphant embryos using ntl and sox17 as specific markers and found that the clustering and migration of DFC was altered, leading to a disorganized KV. Finally, through a combination of wdr18 and itgb1b morpholino injections, we provided evidence that wdr18 and itgb1b genetically interact in the laterality determination process. Thus, we reveal a new and essential role for WD-repeat proteins in the determination and regulation of L-R asymmetry and propose a potential mechanism for wdr18 in the regulation of DFC clustering and migration and KV formation.